Impaired Fibrinolysis in Sickle Cell Disease - Green, D; Kwaan, H. C; Ruiz, G (Thrombosis and Haemostasis, 1970)
Coagulation studies were performed in 52 patients with sickle cell disease during asymptomatic periods and during episodes of crisis and infection. Platelet counts averaged 473,000, 469,000, and 461,000 per mm3 in these 3 groups, and factor VIII concentrations were elevated in all. Fibrinogen was increased to the same extent in both sickle cell and non-sickle cell patients with infection. Fibrinolytic activity, as measured by euglobulin lysis times and zones of lysis on fibrin plates, was markedly reduced during periods of infection in sickle cell patients but not in non-sickle patients. Impairment of fibrinolysis in most patients was not on the basis of overutilization or consumption, since no decrease in the levels of clotting factors or plasminogen was observed. It was suggested that generalized intravascular sickling in these patients may have caused widespread endothelial damage, resulting in decreased production of plasminogen activator.In addition, several sickle cell patients with infection were found to possess elevated levels of an inhibitor directed against urokinase.